Rounds for patient safety: experience at the Instituto Nacional Materno Perinatal - Guevara Ríos, Enrique (2019)
Rounds for patient safety is a recommended practice to increase the quality of clinical and non-clinical services involved in patient care. It consists of planned visits of the relevant executive staff in order to establish direct relationship with personnel and patients with an educational attitude and with the general objective to strengthen the culture of patient safety. In the Instituto Nacional Materno Perinatal, a category III-2 establishment specialized in the care of women, pregnant women and newborns, these rounds have been in practice since 2011, and improvements in safe care for patients have been obtained. We present the experience of the Institute between years 2011 and 2017.